Evaluation of the operation installation manager emergency management training and assessment (oim - emta) program of Sarawak Shell Berhad - Lock, Edward Un Kah (1999)
Safety training programs must be relevant and effective because they are expensive and involve much efforts and resources. To achieve this, evaluations must be effectively conducted and analyzed to determine their strengths and weaknesses, and provide quality improvements. The primary objective of this project was to test a training program evaluation tool, the Program Quality Index (PQI) System. The aim here was to test this tool for practicality, ease of use and implementation. If it is confirmed as such, the intention is to evaluate all the existing training programs of SSB/SSPC to compare their priorities and importance to business impact. The training program selected for the evaluation is the OIM-EMTA program because it is a high priority and HSE critical training program involving senior OIMs and their Deputies. It has not been formally evaluated since its implementation two years ago. The pal method was based on the measurements of four evaluable dimensions of training; Instructional Merit, Learning, Usage of Learning, and Strategic Value. The performance of the overall program and each component could be interpreted from the total and individual components 'scores'. A survey was conducted using questionnaires consisting of two sections: Demography Variables and Training Categories. The questionnaires were sent to all the OIM/SANVS who had undergone the training program. From the responses, the data were processed based on pal system methodology. The overall findings were: • the pal evaluation tool was indeed a simple and practical evaluating tool. The calculations of the measurements of the pal Index and component 'scores' do not require complex mathematics or any software applications. • as for monitoring the quality of the program, the strong and weak components could be easily identified from the variation in POI scores, "flagging" potentially important issues so that further evaluation inquiry can be targeted to improve the overall training program quality. In conclusion, the training pal evaluation tool is recommended as a program quality monitoring and improvement system, and as an objective measure to prioritize training programs.